Virtual reality-based measurement of ocular deviation in strabismus. (March 2020) - Miao, Yinan; Jeon, Jun Young; Park, Gyuhae; Park, Sang Woo; Heo, Hwan
Highlights: The proposed virtual reality-based real-time system completely replaces the diagnostic procedure of a doctor in cover tests, which can be applied in a small space and have a high tolerance for head movements using only a virtual reality headset and a common personal computer. Pupil tracking technique is applied for more objective and accurate observation of eye motion instead of using naked eyes in real examination. Two diagnosis techniques, direct measurement and stepwise approximation, are developed to accurately and efficiently assess the deviation angle in strabismus. Abstract: Background and objective: Strabismus is an eye movement disorder in which shows the abnormal ocular deviation. Cover tests have mainly been used in the clinical diagnosis of strabismus for treatment. However, the whole process depends on the doctor's level of experience, which could be subjected to several factors. In this study, an automated technique for measurement of ocular deviation using a virtual reality (VR) device is developed. Methods: A VR display system in which the screens that have the fixation target are changed alternately between on and off stages is used to simulate the normal strabismus diagnosis steps. Patients watch special-designed 3D scenes, and their eye motions are recorded by two infrared (IR) cameras. An image-processing-based pupil tracking technique is then applied to track their eye movement. After recording eye motion, two strategies for strabismus angle estimation are implemented: direct measurement and stepwise approximation. The direct measurement converts the eye movement to a strabismus angle after considering the eyeball diameter, while the stepwise approximation measures the ocular deviation through the feedback calibration process. Results: Experiments are carried out with various strabismus patients. The results are compared to those of their doctors' measurement, which shows good agreement. Conclusions: The results clearly indicate that these techniques could identify ocular deviation with high accuracy and efficiency. The proposed system can be applied in small space and has high tolerance for the unexpected head movements compared with other camera-based system.